การศึกษาดัชนีชี้วัดความสำเร็จการส่งกำลังบำรุงทางทหารของไทย : ศึกษาเฉพาะกรณีการส่งกำลังบำรุงกองทัพบก - ภารพบ สุภมนัส (Journal of Applied Economics and Management Strategy, 2018)
This Paper aimed to develop key performance indicators for Thailand’s military logistics using mathematical and other suitable models for military logistics key performance indicators. The key performance indicators (KPIs) could support the decision-making of commanders. Moreover, in the case of emergencies and national disasters the mathematics model could be applied to other units involved. The results of the study from the questionnaire data collection revealed that there was agreement at the level of “a lot” that the Royal Thai Army should possess KPIs with international logistics to increase the effectiveness of RTA logistics. In addition, the study of the benchmarking in other services and the Royal Thai Police showed that there was agreement concerning directly introducing logistics tools as KPIs in military logistics. This indicates that in order to enhance the effectiveness of logistics, the Just-In-Time logistics with the right routes to the logistics location are an important KPI of logistics. Applying the Cube Cargo software program can help provide data for the commanders’ decision-making in terms of selecting the most convenient, fastest, and more accurate and reliable routes. However, targeting military objectives and logistics locations is a crucial factor. In conclusion, international logistics tools should be implemented in Thailand’s military logistics. The researcher proposed a suitable model for Thailand’s military logistics including for example the development of Thailand’s mailing logistics network optimization strategy, and the integrity of Thailand’s military logistics in the model “Joint Logistics” with other services, police, civilians, and regular exercises. Recommendations include the following: imposing KPIs for Thailand’s military logistics at direct and international levels, effectively applying the study benefits to be used as a guideline or as a tool for long-term planning as well as the exchange of information with foreign countries. Study and identification of strategic routes for Thailand’s border security throughout the nation are also needed. Moreover, the researcher suggests setting strategic routes of security for logistics along the borders for the benefit of Thailand’s logistics, repatriation, emergency evacuation, and linking other operation and military logistics services at the national level as advanced long-term planning for national defense, including regular updating of plans. Keywords: Military logistics, Army logistics, Key performance indicators